Scenedesmus sp GROWTH IN DIFFERENT CULTURE mediums FOR MICROALGAL PROTEIN PRODUCTION - Catalina QUEVEDO O. (Universidad de Antioquia, 2009)
Microalgae are considered as functional food capable not only of raise nutritional content but also of affect positively the animal’s health and human’s containing important amounts of proteins, vitamins, and polyunsatured fatty acids. Some Microalgae have even higher amino acid content than conventional food; Scenedesmus sp has a lysine level higher than the required for the Food and Agriculture Organization of the United Nations (FAO) and proteins levels between 25 and 35%, becoming a rich protein source. In this study, biomass and protein production of Green microalgae Scenedesmus sp, in different growth mediums, Standard 1, Standard 2 and Algal with NaHCO3 as carbon source, , were evaluated, . Among mediums:. Standard 2 medium had presented the higher biomass production (0.41 g/L) and the Algal medium the higher protein percentage measured by dry weight (35.18%). also, polymorphism presented by the microalgae in each medium was studied; which show morphological changes even among colonies with same cells number. This microalgae has a potential application in animal food industry.